Efficacy of corticosteroid in pulmonary and extrapulmonary tuberculosis - Barmawi Hisyam Barmawi Hisyam (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2001)
Tuberculosis is one of major health problems all over the world. The epidemiologic data shows an increase in its morbidity and mortality. Infection of tuberculosis involves almost every organ of the body, ie. respiratory organ, known as pulmonary tuberculosis and other organs, known as extrapulmonary tuberculosis. The World Health Organization (WHO) has recently published programme guidlines for the treatment of tuberculosis. In certain cases, especially extrapulmonary tuberculosis, a combination of anti-tuberculous drugs and corticosteroid is assumed to be useful.Key words : pulmonary tuberculosis - extrapulmonary tuberculosis - anti tuberculous drug - corticosteroid